Identification of the major QTL QPm.cas-7D for adult plant resistance to wheat powdery mildew - Liu, Hong; Han, Guohao; Gu, Tiantian; Jin, Yuli; Shi, Zhipeng; Xing, Lixian; Yan, Hanwen; Wang, Jing; Hao, Chenyang; Zhao, Meicheng; An, Diaoguo (Frontiers in Plant Science, 2022)
Developing effective and durable host plant resistance is crucial for controlling powdery mildew, a devastating disease caused by Blumeria graminis f. sp. tritici (Bgt). In the present study, we dissected the genetic basis of the adult plant resistance to powdery mildew using a recombinant inbred line (RIL) composed of 176 F9 RILs population derived from a cross between PuBing 3228 (P3228) and susceptible cultivar Gao 8901. P3228 exhibits stable adult-plant resistance to powdery mildew in the field over consecutive years. We identified two QTLs on chromosomes 7DS (QPm.cas-7D) and 1AL (QPm.cas-1A) contributed by P3228, and one QTL on 3DS (QPm.cas-3D) contributed by Gao 8901, which could explain 65.44%, 3.45%, and 2.18% of the phenotypic variances, respectively. By analyzing the annotated genes in the 1.168 Mb physical interval of the major QTL QPm.cas-7D, we locked a previously cloned adult-plant resistance gene Pm38 that was most probably the candidate gene of QPm.cas-7D. Sequence alignment analysis revealed that the candidate gene of QPm.cas-7D in P3228 was identical to the reported Pm38 sequence. Two haplotypes QPm-7D-R and QPm-7D-S were identified in the whole Pm38 genomic regions between P3228 and Gao 8901. To apply QPm.cas-7D in wheat breeding, we developed a kompetitive allele-specific PCR (KASP) marker Kasp5249 that is closely linked with these haplotypes. It is worth mentioning that the QPm-7D-R haplotype significantly decreased TKW and underwent negative selection for higher yields in China wheat breeding. In this study, we identified a major QTL QPm.cas-7D and revealed the relationship between its resistance and yield, which could be beneficial for further applications in wheat disease resistance and high-yield breeding.